Knowledge, mediation and empire : James Tod's journeys among the Rajputs - D'Souza, Florence (Book collections on Project MUSE., 2015)
James Tod (1782-1835) spent 22 years in India (1800-22), during the last five of which he was Political Agent of the British Government in India to the Western Rajput States in north-west India. This book studies Tod's relationships with particular Rajput leaders and with the Rajputs as a group in general, in order to better understand his attempts to portray their history, geographical moorings and social customs to British and European readers.